An insight into the temperature dependence of photoluminescence of a highly-emissive Cs-Ag(Na)Bi(In)Cl-6 perovskite - Stroyuk, Oleksandr; Raievska, Oleksandra; Osvet, Andres; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2023)
The temperature-dependent evolution of the photoluminescence (PL) properties of a highly emissive Cs2Ag0.35Na0.65Bi0.02In0.98Cl6 perovskite was examined in the range of 80-340 K. The PL maximum exhibited a shift to higher energies with an increase in T, while the bandgap decreased with elevated T. This behavior can be explained by a thermal distribution of the self-trapped exciton states.
CRIS-Team WoS Importer:2023-03-17